Retraction Note: High Expression of RIOK2 and NOB1 Predict Human Non-small Cell Lung Cancer Outcomes - Kun Liu; Hong-Lin Chen; Shuo Wang; Ming-Ming Gu; Xin-Ming Chen; Shuang-Long Zhang; Kang-Jun Yu; Qing-Sheng You (Scientific Reports, 2023)
Editor's Note: this Article has been retracted; the Retraction Note is available at https://doi.org/10.1038/s41598-023-32033-5